Impact of Thyroid Hormone Administration on Fluid Requirements and Hepatic Injury Markers in Hemorrhagic Shock Due to Liver Trauma. (1st December 2013) - Karmaniolou, Iosifina; Pantos, Constantinos; Orfanos, Nikolaos; Mylonas, Anastasios; Theodoraki, Kassiani; Staikou, Chryssoula; Stergiou, Eirini; Kostopanagiotou, Georgia; Smyrniotis, Vassilios; Arkadopoulos, Nikolaos
ABSTRACT: Introduction: The aim of the present study was to evaluate the effect of triiodothyronine (T3) administration in a porcine model of hemorrhagic shock due to liver surgery, in terms of hemodynamic stability, acid-base status, and hepatic injury markers. Materials and Methods: Hemorrhagic shock was induced in swine by left lobe liver resection and allowed bleeding to a mean arterial pressure of 35–40 mmHg for 40 min. Animals were randomly assigned into a sham group ( n = 5), a fluid-resuscitated group ( n = 7), and a fluid plus T3-resuscitated group ( n = 7). T3 was given by continuous intravenous infusion from the beginning of the experiment. After the 40 min of shock animals were resuscitated with the aim of restoring mean arterial pressure (±10% from baseline). Resuscitation lasted for 1 hr and then swine were followed for another 460 min (total 6 hr). Blood loss, hamodynamic parameters, fluids administered, acid-base status, and liver enzymes were measured. Results: Blood loss was similar in both groups. Animals treated with T3 required less fluids than swine resuscitated with crystalloids and colloids only (N/S 0.9%: 1071 ± 189 ml vs. 2429 ± 535 ml, Voluven 6%: 550 ± 96 ml vs. 1000 ± 289 ml, p < .05), plus they were less acidotic at the end of the observing period (7.38 ± 0.08 vs. 7.26 ± 0.12, p < .05). Tachycardia was not associated with T3 administration. Hepatic enzymes did not exhibit differences between groups. Conclusion: Our study demonstrates the beneficial impact of T3 administration during controlled hemorrhagic shock and resuscitation. Animals resuscitated with T3 necessitate less amounts of fluids to maintain hemodynamic stability and acid-base status. Moreover, T3 administration does not seem to aggravate blood loss or harm the hepatic tissue.